(untitled) - Khandker, Nurul Alam (Florida, 1963)
The subject of this thesis was selected with the hope that a fisheries development program could be suggested that would be useful to countries where fisheries are still largely underexploited.
Keywords: Phát triển thủy sản,Fisheries development